Laminaria Japonica polysaccharide promotes the expression of calcitonin receptor-like receptor in type 2 diabetes mellitus model mice - Xiao-dan, Li; Li, Shuai; De-lin, Duan; Wenzhen, Lv (JOURNAL OF ADVANCES IN BIOLOGY, 2013)
Amylin, or islet amyloid polypeptide (IAPP), is a 37-residue peptide hormone[1-2]. It is cosecreted with insulin from the pancreatic Î² cells in the ratio of approximatrly 100:1[3-4]. Amylin receptor (AR) is composed of calcitonin receptor (CTR) and receptor activity-modifying proteins (RAMPs) heterodimer. CTR is a senven transmembrane domain. The aim of experiment was to investigate the effect of Laminaria Japonica polysaccharide (LJPS) on the expression of calcitonin receptor-like receptor (CrlR) and hypoglycemic activity in type 2 diabetes mellitus mice. Type 2 diabetes mellitus models were established by feeding high fatty forage and injecting alloxan in 40 healthy male mice. The LJPS was applied as additive in physiological saline to treat the mice by intragastric administration. The levels of fasting blood glucose (FBG) were detected by automatic blood glucose device. The tissue morphology of brainstem, liver and pancreas were analyzed by Hematoxylin-eosin assay. The expression of CrlR was determined by immunohistochemisty and Western blot, and the expression of CrlR mRNA was detected by RT-PCR. The results indicated after treated with LJPS, the serum level of FBG were significantly higher than that in model group (Pï¼œ0.05). The morphology and structure of liver and pancreas tissue improved than those in model group. The expressions of CrlR mRNA and CrlR protein were significantly higher than those in model group (Pï¼œ0.05). These results suggest that LJPS could play a hypoglycemic effect by promoting the expression of CrlR in liver and pancreatic tissue to lessen insulin resistance.